Sustainable approaches to urban transport - Mohan, Dinesh 1945-; Tiwari, Geetam (Boca Raton, FL Taylor & Francis Group, 2020)
"As cities become increasingly congested current transport patterns are unsustainable: heavy in energy use, high in economic and environmental cost, and exacerbating inequity between those who can access high speed travel and those who cannot. Good urban planning develops human-scale cities and encourages modes such as bicycles, increased zones exclusive to pedestrians within the cities, and changed fiscal policies to incentivise public over private transport. Equally, it requires good engineering design to manage road use. This book brings together contributions from leading international experts in urban planning, transport and governance who suggest changes to make our cities more sustainable in the face of climate change. All professionals working in transport and engineering and planning students will find an overview of a broad field in this interdisciplinary collection of essays."--Provided by publisher.
Urban transportation planning -- From myth to science in urban and transport planning -- The neo-liberal urban development paradigm and transport related civil society responses in Karachi, Pakistan -- City design and transport: observations at different urban scales -- Urban layouts, densities and transportation planning -- Coming to terms with the complexity of Indian urbanism -- Urban mobility: is anyone incharge? -- Railroading the rules: transport, government, and stakeholders -- City governance and effectiveness -- Alternative transport policies for personal public transport: lessons learned -- The changeable shape of the city -- Moving transport: injecting transportation planning in Nairobi's metropolitan land-use agenda -- Urban public transport and economic development -- Urban mobility in China: developments in past twenty years -- The potential of casualty prevention in road traffic -- Health effects of transport -- Traffic safety, city structure, technology and health -- Paratransit in the developing world -- Paratransit, taxis and non-motorised transport: a review of policy debates and challenges -- Paratransit and non-motorised traffic as mainstream road users -- Politics of mobility and the science of sustainability.
Keywords: Urban transportation -- Planning; Urban transportation -- Environmental aspects; Transportation -- Safety measures; Sustainable urban development